Ax+b=cx+b

Simple and best practice solution for Ax+b=cx+b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Ax+b=cx+b equation:


Simplifying
Ax + b = cx + b

Reorder the terms:
b + xA = cx + b

Reorder the terms:
b + xA = b + cx

Add '-1b' to each side of the equation.
b + -1b + xA = b + -1b + cx

Combine like terms: b + -1b = 0
0 + xA = b + -1b + cx
xA = b + -1b + cx

Combine like terms: b + -1b = 0
xA = 0 + cx
xA = cx

Solving
xA = cx

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1cx' to each side of the equation.
-1cx + xA = cx + -1cx

Combine like terms: cx + -1cx = 0
-1cx + xA = 0

Factor out the Greatest Common Factor (GCF), 'x'.
x(-1c + A) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(-1c + A)' equal to zero and attempt to solve: Simplifying -1c + A = 0 Reorder the terms: A + -1c = 0 Solving A + -1c = 0 Move all terms containing x to the left, all other terms to the right. Add '-1A' to each side of the equation. A + -1A + -1c = 0 + -1A Combine like terms: A + -1A = 0 0 + -1c = 0 + -1A -1c = 0 + -1A Remove the zero: -1c = -1A Add 'c' to each side of the equation. -1c + c = -1A + c Combine like terms: -1c + c = 0 0 = -1A + c Simplifying 0 = -1A + c The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

x = {0}

See similar equations:

| 300/1760=x/1 | | T(u+3v)=w-5u | | x+15=50 | | 4n=5n-6n+20 | | 3m-n=2m+m | | -19=f/6 | | 5(13-9)= | | x^5-4x^3+8x^2-32=0 | | -5p-(-9w)+3-4w+2p-7= | | 25x^2-35x=-12 | | X(9x+3)=4x^2-21x+5 | | x/x+8=y/7 | | -7.5k+55.2=15.3 | | (2u+7)(8-u)=0 | | y/y+8=x/7 | | 2z+4z=5z-9 | | 84x+105x=4998 | | X(9x+1)=4x^2-8x+2 | | x^2+x=64 | | z/z^2 | | -1+2y=-4 | | 1+2y=-4 | | 9n^9-36n^8-540n^7=0 | | x=-96-3x | | 84x+105(3-x)=4998 | | y=144-3(48-y) | | 84x+105(x-3)=4998 | | -3x+5=2x | | 2/3x+6=27 | | 7/2x+1/2x=3x+3/2+5/2 | | 6x-12-4=16 | | y=0.28y |

Equations solver categories